1958
DOI: 10.1161/01.cir.17.4.750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Intravenous Sodium Chloride Load on Renal Hemodynamics and Electrolyte Excretion in Essential Hypertension

Abstract: Excretion of infused sodium, chloride, and water increased proportionately in patients with progressively more severe grades of hypertension and of increased renal vascular resistance. These relationships held so long as renal plasma flow and glomerular filtration rate were not greatly impaired. The abnormality was characterized by increased renal tubular rejection of sodium, chloride and water.T HAT most hypertensive patients excrete more water, sodium, and chloride than do normotensive patients when given so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1960
1960
1990
1990

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 15 publications
(3 reference statements)
0
24
0
Order By: Relevance
“…Further, it was found in the present study that the excretion of Na became greater with an advance of hypertension as far as the renal function was normal. It seems, as indi cated by Cottier,13) that the " high salt-excretor " corresponds with the stage where the renal function is not impaired and the " normal salt excretor " with the stage where the renal function is damaged.…”
Section: Effect On Minute Electrolytes Excretionmentioning
confidence: 94%
“…Further, it was found in the present study that the excretion of Na became greater with an advance of hypertension as far as the renal function was normal. It seems, as indi cated by Cottier,13) that the " high salt-excretor " corresponds with the stage where the renal function is not impaired and the " normal salt excretor " with the stage where the renal function is damaged.…”
Section: Effect On Minute Electrolytes Excretionmentioning
confidence: 94%
“…However, this pattern has been described in subjects with established hypertension and in response to an acute saline load producing rapid extracellular volume expansion. 33 " 35 More recent investigations have demonstrated a heterogeneity in sodium excretion rates after saline loads in hypertensive patients. 36 Rydstedt et al 37 studied sodium excretion rates after saline infusion in hypertensive individuals grouped by before sodiumloading renin levels.…”
Section: -29mentioning
confidence: 99%
“…Numerous investigators have demonstrated that acute volume expansion in patients with hypertension results in a more prompt rise in sodium excretion than is seen in the normotensive subject (1)(2)(3). This phenomenon, which has been referred to as an "exaggerated natriuresis," has been attributed both to decreased tubular sodium reabsorption (2,3) and to increased glomerular filtration rate (GFR) (2), but the intrarenal mechanisms have not been precisely defined.…”
Section: Introductionmentioning
confidence: 99%